Narrating war and peace in Africa - Falola, Toyin 1953-; Haar, Hetty ter (Rochester studies in African history and the diaspora, 2010)
Narrating War and Peace in Africa interrogates conventional representations of Africa and African culture -- mainly in the twentieth and early twenty-first centuries -- with an emphasis on portrayals of conflict and peace. While Africa has experienced political and social turbulence throughout its history, more recent conflicts seem to reinforce the myth of barbarism across the continent: in Nigeria, Rwanda, Somalia, Sierra Leone, Uganda, Kenya, Mozambique, Chad, South Africa, Zimbabwe, and Sudan. The essays in this volume address reductive and stereotypical assumptions of postcolonial violence as "tribal" in nature, and offer instead various perspectives -- across disciplinary boundaries -- that foster a less fetishized, more contextualized understanding of African war, peace, and memory. Through their geographical, historical, and cultural scope and diversity, the chapters in Narrating War and Peace in Africa aim to challenge negative stereotypes that abound in relation to Africa in general and to its wars and conflicts in particular, encouraging a shift to more balanced and nuanced representations of the continent and its political and social climates. Contributors: Ann Albuyeh, Zermarie Deacon, Alicia C. Decker, Aména Moïnfar, Kayode Omoniyi Ogunfolabi, Sabrina Parent, Susan Rasmussen, Michael Sharp, Cheryl Sterling, Hetty ter Haar, Melissa Tully, Pamela Wadende, Metasebia Woldemariam, Jonathan Zilberg. Toyin Falola is the Jacob and Frances Sanger Mossiker Chair in the Humanities and University Distinguished Teaching Professor at the University of Texas at Austin. Hetty ter Haar is an independent researcher in England